2015
DOI: 10.1007/s10522-015-9606-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of longevity and fecundity at two temperatures in a set of heat-selected recombinant inbred lines of Drosophila melanogaster

Abstract: Quantitative trait loci (QTL) were mapped for longevity and fecundity at two temperatures, 20 and 30 °C, in two sets of recombinant inbred lines (RIL) highly differing in thermotolerance. Early fecundity (EF) and longevity showed a negative association between temperatures. For instance, longevity was higher and fecundity was lower in the RIL panel showing higher life span at 30 °C. One X-linked QTL (7B3-12E) co-localized for longevity and EF at 20 °C, with one QTL allele showing a positive additive effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The oviposition surface consisted of a solution of agar (1.5 g) and water (140 ml) plus 0.2 ml of food coloring and yeast paste. Food coloring (Fleibor Laboratory, La Tablada, Buenos Aires, Argentina) was added to facilitate the observation of all eggs and egg shells (Sambucetti et al., ). The eggs were counted on the spoons using a stereo microscope every 2 days, when flies were transferred to new vials with fresh spoons.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The oviposition surface consisted of a solution of agar (1.5 g) and water (140 ml) plus 0.2 ml of food coloring and yeast paste. Food coloring (Fleibor Laboratory, La Tablada, Buenos Aires, Argentina) was added to facilitate the observation of all eggs and egg shells (Sambucetti et al., ). The eggs were counted on the spoons using a stereo microscope every 2 days, when flies were transferred to new vials with fresh spoons.…”
Section: Methodsmentioning
confidence: 99%
“…Several QTL mapping studies revealed some potentially pleiotropic regions with effects on both stress resistance and longevity (Vieira et al., ; Wang et al., ; Defays et al., ; Rodriguez et al., ; Sambucetti et al., ), suggesting an association of the genetic variation for stress resistance with longevity. Previous studies in Drosophila melanogaster Meigen (Diptera: Drosophilidae) have found a major QTL affecting heat resistance in the middle of chromosome 2 (Norry et al., , 2007a, ; Morgan & Mackay, ; Arias et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations